Exposure-response relationships for hexahydrophthalic and methylhexahydrophthalic anhydrides with total plasma protein adducts as biomarkers - Rosqvist, Seema; Nielsen, Jorn; Welinder, Hans; Rylander, Lars; Lindh, Christian H; Jönsson, Bo AG (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This study investigated the exposure-response relationships of hexahydrophthalic anhydride (HHPA) and methylhexahydrophthalic anhydride (MHHPA) and evaluated the applicability of the total plasma protein adducts (TPPA) of these anhydrides as biomarkers of exposure and risk. ' ' METHODS ': 'In a cross-sectional study of 139 workers in a plant manufacturing electrical capacitors, the long-term exposure to HHPA and MHHPA was assessed through the quantification of TPPA using gas chromatography-mass spectrometry. Smoking and medical histories were obtained through questionnaires. Work-related symptoms of the eyes and airways were recorded. Specific immunoglobulin (Ig) E (radioallergosorbent test) and IgG (enzyme-linked immunosorbent assay) were determined in serum. ' ' RESULTS ': 'The mean level of the TPPA of HHPA was 840 fmol/ml and that of the TPPA of MHHPA was 1700 fmol/ml. There was no correlation between the TPPA of HHPA and the TPPA of MHHPA. Of all the workers, 19% were found to be positive for specific IgE and 17-19% for IgG. Positive associations were observed between HHPA exposure and specific IgE and IgG, respectively, and between MHHPA exposure and specific IgG. Regarding work-related symptoms, 27% of the workers had symptoms from the nose, 21% had symptoms from the eyes, 11% had symptoms from the lower airways, and 8% had nose bleeding. There were significant exposure-response relationships for symptoms of the eyes and nose for HHPA exposure. ' ' CONCLUSIONS ': 'The results show that there is an exposure-response relationship for HHPA both with specific antibodies and with work-related symptoms and down to adduct levels of 40 fmol/ml plasma. In addition, the results elucidate the potential power of TPPA as a relevant index of exposure and risk.
Keywords: biomarker; exposure-response relationship; hexahydrophthalic anhydride; methylhexahydrophthalic anhydride; phthalic anhydride; protein adduct; total plasma protein adduct